Prevalence of depression among elderly in an urban setting of Southern India - Girijammal, Remya; Varghese, Sara; Haridasan, Retheesh K.; Indu, Pankajakshan V. (International Journal Of Community Medicine And Public Health, 2022)
Background: The reported prevalence of depression by WHO in the elderly varied between 10% to 20% in various societies. Some of the 121community-based studies in India had reported a prevalence of 13 to 43% depression in elderly. Kerala had a 12.8% of geriatric population according to census 2011. The aim of the study was to find out the prevalence of depression among geriatric population in an urban area which comes under Thiruvananthapuram Corporation, Kerala state, India. Methods: Study design is cross sectional. Elderly over 60 years were interviewed using PHQ -9 questionnaire. Depression is diagnosed when the total score is equal to more than 5 in PHQ-9 questionnaire. Results: Total 405 elderly were included in the study. 195 (52%) were females and 213 (48%) were males. The prevalence was found to be 37.3% (CI, 30.78-43.98). Among them mild and moderate depression accounted for majority of cases (35.7%) than severe depression (1.5%). Bivariable analysis yielded factors such as previous history of mental illness, family history of mental illness, stress and absence of recreation that were associated with the development of depression. Family history of mental illness (adjusted OR 4.59) and stress (adjusted OR 7.43) were emerged as predictors of depression in this study in multivariable analysis. Conclusions: Prevalence of depression in elderly was found to be 37.3% (30.78-43.98) in an urban population of Sothern Kerala. In logistic regression analysis family history of mental illness and stress were emerged as independent predictors of depression among elderly.